DEVELOPING A JOB SATISFACTION MAP: IMPLEMENTING AHP IN THE FINANCIAL TECHNOLOGY (FINTECH) INDUSTRY ENVIRONMENT - Hafsah Aldrianty; Nidya Dudija (Journal of Economic, Bussines and Accounting (COSTING), 2024)
This study seeks to address three primary inquiries: firstly, to establish priority criteria for selecting job satisfaction factors; secondly, to identify priority sub-criteria in the selection of these factors; and thirdly, to determine the most crucial factors influencing employee job satisfaction. Employing the Analytic Hierarchy Process (AHP) method, the research serves as an analytical tool to resolve the complexities of selecting job satisfaction factors and aids companies in establishing assessment criteria for these factors. The study focuses on three criteria categories—financial, social, and work environment factors—for measuring employee job satisfaction. Each criterion encompasses various relevant sub-criteria for evaluating job satisfaction. Utilizing the AHP method, the research analyzes assessment outcomes with a quantitative scale from 1 to 9, assessing the relative importance of each unit in comparison to others. Concentrating on factors impacting employee satisfaction in the information technology sector, this research offers a unique perspective compared to previous studies. The aim is to conclude and compare the influencing factors on employee job satisfaction levels in IT companies. The study's contribution lies in providing a comprehensive view of priorities and sub-priorities in the selection of job satisfaction factors.